Organizing societal space within globalization: Bringing society back in - Arndt Sorge (Max Planck Institute for the Study of Societies, 1999)
The notion of 'society' is increasingly debated, recently, under the impact of 'globalization'. This debate is carried out in both sociology and business studies, and it also has implications in political theory. A theoretical grounding of society is provided following G.H. Mead, which bears sufficient regard to actors and avoids determinism. Society is conceptualized as 'societal space', open to layering in different forms. Incongruent layering is then put forward as a feature of societal evolution which has hitherto been neglected as an engine of modernization. This form of layering is also suggested to be important for current debates. Following this concept, the business and organizational literature can be linked with social theory in a way which shows how 'provincialization' of identity, institutions and culture is pervasively linked with the extension of horizons of action under globalization. Various comparative findings are adduced to show how the dialectics of globalization and provincialization work, and how socio-institutional patterns interact with the evolution of enterprise strategies in order to fuel this dialectic. In such an evolution, society has an important part to play. But this is not because society re-asserts itself as a co-extensive entity on a higher plane. Instead, it is precisely the layering of societal space which makes societal effects a necessary concept.
Keywords: 300